Factors Influencing the Utilization of Reproductive Health Services among Adolescents with Disabilities: A Review - Rhadiyah, Putri; Adnani, Qorinah Estiningtyas Sakilah; Akhiat, Akhiat (Universitas Aisyah Pringsewu, 2024)
The global population of individuals with disabilities is approximately 1.3 billion people, constituting approximately 16% of the total world population. Individuals with disabilities are at a heightened risk of experiencing discrimination, including but not limited to restricted availability of healthcare services and instances of sexual violence. A limited proportion of adolescents with disabilities avail themselves of reproductive health information and education services due to their perception that such programs are inaccessible and lacking in inclusivity for individuals with disabilities. The objective of this scoping study is to examine the factors that impact the utilisation of reproductive health services among adolescents with disabilities. This article employs the PRISMA method to conduct a scoping review, aiming to identify articles published within the last five years (2019-2023) from various databases, including ProQuest, SAGE Journal, Science Direct, and Cochrane. The review yielded a total of seven relevant journals. The findings indicate that there is a low utilisation of reproductive health services among adolescents with disabilities. This can be attributed to several factors, such as limited knowledge, lack of partner support, inadequate media exposure, existing policies, and the negative perceptions held by adolescents with disabilities regarding the quality of reproductive health services available to individuals with disabilities.